In silico exploration the phenolic compound of olive leaves as acetylcholinesterase enzyme (AChE) inhibitor for Alzheimer’s disease therapy - Nurul Jadid Mubarakati; Oktavia Rahayu Puspitarini; Tintrim Rahayu; Alik Maulidiyah (The East Java Biological Society, 2019)
Olive (Olea europaea) have been cultivated and grown well in tropical climates such as Indonesia. Indonesia local community have used olive as herbal medicines due to its active compounds known as oleuropein that has many biological activities including as neurotherapy in Alzheimer's disease. The purpose of this study is to explore the potential phenolic compounds of olive and examine the acetylcholinesterase (AChE) inhibitory activity displayed by different olive polyphenols through a silico approach. The bioactive compounds of olive which had been analyzed in this study were phenolic compound included oleuropein, demethyl-oleuropein, ligstroside, oleoside, verbascoside, luteolin 7-glucoside, and hydroxytyrosol. Interaction of bioactive compounds with acetylcholinesterase (AChE) was analyzed through molecular specific docking using AutoDock Vina with Pyrx Software. The result elucidate that olive contain potential biological activities as antioxidant, anti-inflammatory, antineoplastic, free radical scavenger, antibacterial, antifungal, expression TP53 enhancer, caspase 8 stimulant, platelet adhesion inhibitor, treatment for lipoprotein disorder, antiviral and dementia treatment/Alzheimer disease. The highest bioactivity percentage of olive phenolic compound are as an antioxidant of 82%, anti-inflammatory of 73%, and anti-cancer (antineoplastic) of 70% respectively. Based on molecular docking analysis show one of olive phenolic compound of the dimethyl-oleuropein has strong interaction with AChE as pointed in the binding affinity of demethyl-oleuropein +AChE of -8.9 kcal/mol has closed to galanthamine binding affinity of -10.3 kcal/mol. Along with glutamate acid 202, tyrosine 133 and tyrosine 124 are the major contributors in the target-ligand interactions. The selected demethyl-oleuropein ought to be tested in clinical studies to discover new neuro-therapeutic candidates.